Effectiveness of an eHealth intervention to improve subjective well‐being and self‐efficacy in cardiovascular disaease patients: A pilot non‐randomized controlled trial - Naima Z. Farhane‐Medina; Rosario Castillo‐Mayén; Carmen Tabernero; Sebastián J. Rubio; Tamara Gutiérrez‐Domingo; Esther Cuadrado; Alicia Arenas; Bárbara Luque (Wiley, 2023)
Abstract Aim To evaluate the effectiveness of a multicomponent, eHealth‐based self‐efficacy intervention to promote subjective well‐being and self‐efficacy in patients with cardiovascular disease, exploring sex differences. Design A pilot study of a two‐arm non‐randomized controlled trial. Methods Forty‐two cardiovascular patients (31% women) participated in the study. The experimental group received a personalized psychoeducational session and a 14‐days eHealth intervention. Subjective well‐being (positive and negative affect) and self‐efficacy (chronic and cardiac) were assessed at baseline, post‐psychoeducational session, post‐eHealth intervention and at two follow‐ups. Results The levels of the experimental group in positive affect, at post‐eHealth and follow‐up 1, and self‐efficacy, at post‐eHealth, and both follow‐ups, were statistically significantly higher compared to the control group (all ps < .05). When considering sex, the intervention was effective only for men. The results highlight the potential of eHealth interventions for cardiac patients and underline the importance of considering a gender perspective in their treatment.